Assessing ecotourism in a mountainous landscape using GIS – MCDA approaches. (October 2022) - Khazaee Fadafan, Fatemeh; Soffianian, Alireza; Pourmanafi, Saeid; Morgan, Mark
Abstract: Creation of spatial models are of utmost importance for tourism development in environmentally vulnerable areas. This paper aims to classify a mountainous landscape, Fereydounshahr Township (Iran), using a naturalness continuum with respect to ecotourism potential. In doing so, a conceptual model was developed that consisted of two clusters (natural and anthropogenic), including nine attributes. A Best Worst Method (BWM) was applied for weighting of the criteria. Results indicated that the presence of wildlife scored the highest value, whereas visibility of power lines was the lowest. A Weighted Linear Combination (WLC) was used for combining the criteria to produce a reliable map for ecotourism development, as measured by a sensitivity analysis. It consisted of five classifications: extremely natural (V); highly natural (IV); moderately natural (III); marginally natural (II); and not natural (I). Findings revealed that nearly 60% of the area was covered by Class IV and V, indicating a high degree of naturalness throughout the region. Owing to the fragile nature of the environment, tourism development at this location should focus on hard, rather than soft ecotourists (i.e., minimal development). This same methodology can be used by managers to adopt appropriate strategies regarding possible development options at other tourism destinations, worldwide. Highlights: This paper is the first application of Best Worst Method in naturalness mapping respect to ecotourism. The most effective criteria for the natural classification in a mountainous landscape are identified. The naturalness map is generated in different categories from strongly natural to developed landscapes. The sensitivity analysis is performed for checking the spatial stability of results for the final naturalness map. Appropriate ecotourism activities are suggested based on the naturalness degree of the area.